Correction to: A critical narrative inquiry to understand the impacts of an overdose prevention site on the lives of site users - Abe Oudshoorn; Michelle Sangster Bouck; Melissa McCann; Shamiram Zendo; Helene Berman; Jordan Banninga; Marlene Janzen Le Ber; Zayya Zendo (BMC, 2021)
After publication of the original article [1], the authors identified an error in the author name of Marlene Janzen Le Ber. The given name and family name were erroneously transposed.